PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA DENGAN MENGGUNAKAN MULTIMEDIA DI SEKOLAH DASAR - Sukma, Dede Maulana; Suryani, Suryani; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this research is does the use of Multimedia able to improve the result of students' learning on the learning of science in class VB in Elementary School of 35 South Pontianak?The purpose of this research is to describe the improvement of students' learning result through the Multimedia. The method which is used is the descriptive method, the form of research is action research. With the characteristic of collaborative research. This research was applied through three cycle. The result of research which obtained is the capability of teacher in having the plan of learning through the use of Multimedia in first cycle with 3,03; second cycle 3,42; third cycle 3,77. The result of students' learning through the use of multimedia in first cycle 1 which is 70,81%, cycle 2 is 71,35%, cycle 3 is 71,35%. Based on the conclusion we could suggest that through the use of multimedia in the learning process, it can be the option in improving the students' learning result in science learning. Keywords: Learning Result, Multimedia, Natural Science